Oil Price Fluctuations and Exchange Rate in Selected Sub-Saharan Africa countries: A Vector Error Correction Model Approach - Ehikioya, Benjamin Ighodalo; Omankhanlen, Alexander Ehimare; Babajide, Ayopo Abiola; Osuma, Godswill Osagie; Omodero, Cordelia Onyinyechi (International Journal of Energy Economics and Policy, 2020)
This study employs the Johansen cointegration and the vector error correction model (VECM) to assess the dynamic relationship that exists between oil price fluctuations and the real exchange rate in selected Sub-Saharan Africa countries from January 2004 to December 2017. The result of the monthly data analysis provides evidence to support a cointegration between oil prices and the real exchange rate in sub-Saharan oil dependent nations. The results of the study established a long-run equilibrium connection between fluctuations in oil price and the real exchange rate. Importantly, the study demonstrates the significant power of oil prices to predict the movement of real exchange rates in Nigeria, Angola, the Republic of Congo, Equatorial Guinea and Gabon. This study has implications not only for investors and industry leaders but also for policymakers responsible for the growth and stability of the economy. The results of this study also attest to the need for urgent economic diversification to other sectors of the economy both to reduce the negative influence of oil price fluctuations and to boost economic growth. Keywords: Oil price; Exchange rates; Sub-Sahara; Cointegration; Economy JEL Classifications: C32, F31, F32, F41, Q43 DOI: https://doi.org/10.32479/ijeep.9822